PENERAPAN MODEL PEMBELAJARAN KOOPERARIF TIPE MAKE A MATCH BERBANTUAN MEDIA FLASH CARD PADA PEMBELAJARAN IPAS KELAS V SD NEGERI 32 LUBUK LINGGAU - Zahra Fisyabila, Athaya; Gusti Satria, Tio; Sujarwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the learning mastery of Grade V students in Science and Social Studies (IPAS) at SD Negeri 32 Lubuklinggau after the implementation of the Make A Match cooperative learning model assisted by Flash Card media. The main problem addressed in this study was the low student learning outcomes, with only 25% of students achieving the minimum mastery criterion. This research employed an experimental method using a one-group pretest-posttest design. The sample consisted of 24 students from Class V.A. Data were collected through an objective test and analyzed using a one-sample t-test. The results showed that the mean score increased from 46.11 on the pretest to 78.61 on the posttest. The hypothesis testing indicated that the calculated t-value (4.061) was higher than the critical t-value (1.714), leading to the conclusion that the implementation of the Make A Match cooperative learning model assisted by Flash Card media significantly improved students' learning mastery in Science and Social Studies (IPAS) for Grade V students at SD Negeri 32 Lubuklinggau.